2002
DOI: 10.1063/1.1453943
|View full text |Cite
|
Sign up to set email alerts
|

Empirical mapping of Ni–Mn–Ga properties with composition and valence electron concentration

Abstract: A range of Ni–Mn–Ga alloy compositions close to the stoichiometric Heusler composition, Ni2MnGa, has been reported to show field-induced strains of several percent. Such observations, and the magnitude of the strain observed, depend on the values of several critical material parameters, most importantly the martensitic transformation temperature (Tmart), Curie temperature (TC), saturation magnetization (Ms), strength of the magnetocrystalline anisotropy, and the details of the martensite structure. Here, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
130
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(142 citation statements)
references
References 16 publications
11
130
1
Order By: Relevance
“…For example, replacing Mn by Co, Ni, or Cu increases T M , but the value of T M for Ni 2 Mn 1−x Fe x Ga decreases with increasing Fe concentration x. Several authors have shown that the number of e/a is closely related to the value of T M for Ni-Mn-based FSMAs: a large e/a value indicates a high T M [31][32][33]. However, a larger e/a corresponds to a lower T M for Ni 2 Mn 1−x Fe x Ga as mentioned above.…”
Section: Purpose Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, replacing Mn by Co, Ni, or Cu increases T M , but the value of T M for Ni 2 Mn 1−x Fe x Ga decreases with increasing Fe concentration x. Several authors have shown that the number of e/a is closely related to the value of T M for Ni-Mn-based FSMAs: a large e/a value indicates a high T M [31][32][33]. However, a larger e/a corresponds to a lower T M for Ni 2 Mn 1−x Fe x Ga as mentioned above.…”
Section: Purpose Of This Studymentioning
confidence: 99%
“…The elastic constants of a Ni 0.50 Mn 0.284 Ga 0.216 single crystal were studied by using the ultrasonic continuous-wave method [14]. They investigated the C 11 , C 33 , C 66 , and C 44 modes, and found that every mode exhibited abrupt softening around T M . This lattice softening appears to be affected by the abrupt expansion that occurs just above T M when cooling from the austenite phase.…”
Section: Magnetostriction and Magnetic Field-induced Strain Of Ferroamentioning
confidence: 99%
“…It was established 6,7 that for Ni-Mn-Ga, the phase stability is controlled by the average number of valence electrons per atom. In Fig.…”
mentioning
confidence: 99%
“…It is widely accepted that the valance electron concentration, e/a, affects the transformation temperature in Ni-Mn-Ga alloys [23,24]. The number of valence electrons is assumed to be 10 for Ni, 7 for Mn, 3 for Ga and 9 for Co.…”
Section: Phase Transformation Temperaturesmentioning
confidence: 99%